Использование зон безопасности при эвакуации людей из высотных зданий при пожаре - Pastukhov, Сергей; Zaychuk, К. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
Distinct characteristics from point of view of the fire hazard of high-rise buildings are presented in comparison to less stored buildings. The urgency of the application of security zones in high-rise buildings is substantiated. The recommendations on the justification of security zones and their placement in a high-rise building, the number of floors in the group of notification are developed.